Factors Influencing Mode of Study Preferences in Post-Graduate Business Students - Ladyshewsky, Rick; Taplin, Ross (Learning and Teaching Support Network Centre for Business, Management and Accountancy, Business Education Support Team, 2013)
Post graduate management education has been strongly influenced by information technologyand increasing demands for more flexible delivery. Programs have responded bymaintaining traditional face to face teaching, but increasing intensive and fully onlineofferings. In this research, students were asked why they chose a specific mode of learning,whether it met their expectations and the extent to which they learned. Traditional face toface learning appeared to be the preferred method of learning. Intensive and onlinelearning was used to balance work and lifestyle pressures and/or to deal with geography.While learning style had some influence, most learners, felt they would learn more ina traditional format. Learners selecting intensive mode appeared to be more focussed onbalancing work and lifestyle needs with their education and appeared less concernedabout learning benefits. Learners selecting the fully online option appeared to be challengedby online interactivity and suggested preference for a more traditional face to faceexperience, even though the overall findings suggest they reported the most amount oflearning. Understanding the reasons why specific modes of study are selected is importantwhen making for academic programming decisions as courses move to more flexibledelivery modes.